ANALISIS ASPEK SOSIAL DALAM NOVEL BUMI KARYA TERELIYE - Ayu Angely Galingging; Mutiara Fauziah Putrimina (FKIP, Universitas Palangka Raya, 2023)
This study discusses social aspects in Tereliye's novel Bumi. The purpose of this study is to describe the social aspects of Tere Liye's novel Bumi. This study uses a literary sociology approach to examine literary works related to the social aspects contained therein. This research method is descriptive qualitative. The data source for this research is the novel Bumi by Tereliye. The technique of this research is reading technique and note taking technique. Data analysis was obtained through five stages of analysis, namely reading, identifying, recording, describing and concluding. The results of the study show that there are three social aspects contained in the Bumi novel, namely cultural aspects in the form of norms, historical symbols and general views on life shared by members of a society. While the social environmental aspects are in the form of social relations, profession and crime, the economic aspects are in the form of income and lifestyle.